Digitalization and Public Sector Transformations - Schou, Jannick (Springer International Publishing, 2018)
'Jannick Schou and Morten Hjelholt have written an important contribution to the literature on the evolution of digital public services. Rather than defaulting to the technocratic narratives of many writers, they demonstrate that digitalization is part of an ideological project. This book should be read by everyone interested in electronic government.' - Karl Löfgren, Associate Professor, School of Government, Victoria University of Wellington. This book provides a study of governmental digitalization, an increasingly important area of policymaking within advanced capitalist states. It dives into a case study of digitalization efforts in Denmark, fusing a national policy study with local institutional analysis. Denmark is often framed as an international forerunner in terms of digitalizing its public sector and thus provides a particularly instructive setting for understanding this new political instrument. Advancing a cultural political economic approach, Schou and Hjelholt argue that digitalization is far from a quick technological fix. Instead, this area must be located against wider transformations within the political economy of capitalist states. Doing so, the book excavates the political roots of digitalization and reveals its institutional consequences. It shows how new relations are being formed between the state and its citizens. Digitalization and Public Sector Transformations pushes for a renewed approach to governmental digitalization and will be of interest to scholars working in the intersections of critical political economy, state theory and policy studies.